Public value co-creation : a multi-actor & multi-sector perspective - Sancino, Alessandro (Emerald points., 2022)
Public Value Co-Creation: A Multi-Actor & Multi-Sector Perspective addresses a fundamental gap in the scholarly field of Public Management relating to the advice and strategies available on what public managers can and/or should do to co-create public value. Alessandro Sancino offers a timely and unique approach providing a map with the main actors and their relative domains (public organization; inter-organizational; civic/community) to help guide the strategic thinking of a public manager for designing and leading processes of public value co-creation. The book discusses the concept of public value co-creation from a multi-actor and multi-sector perspective as an opportunity for transforming the public sector, for transitioning business models towards sustainable development and for rejuvenating democracy. Public Value Co-Creation: A Multi-Actor & Multi-Sector Perspective is a great aid to researchers and practitioners committed to achieve public value.